The Effect of Compensation and Work Discipline on Employee Performance with Work Motivation as an Intervening Variable - Rahmi Andini Syamsuddin; Angga Pratama; Denok Sunarsi; Azhar Affandi (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
The purpose of this study to determine and analyze the effect of compensation and work discipline with motivation as a mediation variable. The independent variables in this study are Compensation and Work Discipline. While the dependent variable is performance and the mediating variable is motivation. The number of research samples were 57 respondents using purposive sampling technique. Based on the results of path analysis using smartPLS 3.0, it shows that there is a positive and significant influence between compensation on employee performance, there is a positive and significant influence between work discipline on employee performance. Work motivation mediates the effect of compensation on employee performance. Work motivation mediates the effect of work discipline on employee performance.